Production of taxadiene by engineering of mevalonate pathway in Escherichia coli and endophytic fungus Alternaria alternata TPF6. Issue 4 (15th March 2017) - Bian, Guangkai; Yuan, Yujie; Tao, Hui; Shi, Xiaofei; Zhong, Xiaofang; Han, Yichao; Fu, Shuai; Fang, Chengxiang; Deng, Zixin; Liu, Tiangang
Abstract: Taxol (paclitaxel) is a diterpenoid compound with significant and extensive applications in the treatment of cancer. The production of Taxol and relevant intermediates by engineered microbes is an attractive alternative to the semichemical synthesis of Taxol. In this study, based on a previously developed platform, the authors first established taxadiene production in mutant E. coli T2 and T4 by engineering of the mevalonate (MVA) pathway. The authors then developed an Agrobacterium tumefaciens ‐mediated transformation (ATMT) method and verified the strength of heterologous promoters in Alternaria alternata TPF6. The authors next transformed the taxadiene‐producing platform into A. alternata TPF6, and the MVA pathway was engineered, with introduction of the plant taxadiene‐forming gene. Notably, by co‐overexpression of isopentenyl diphosphate isomerase (Idi), a truncated version of 3‐hydroxy‐3‐methylglutaryl‐CoA reductase (tHMG1), and taxadiene synthase (TS), the authors could detect 61.9 ± 6.3 μg/L taxadiene in the engineered strain GB127. This is the first demonstration of taxadiene production in filamentous fungi, and the approach presented in this study provides a new method for microbial production of Taxol. The well‐established ATMT method and the known promoter strengths facilitated further engineering of taxaenes in this fungus. Abstract : The production of taxanes by engineered microbes is an attractive alternative to the semichemical synthesis of Taxol. In this study, the authors first established taxadiene production platform in Escherichia coli by engineering of the mevalonate pathway, then introduced the taxadiene‐producing platform into Alternaria alternata TPF6 by the established Agrobacterium tumefaciens ‐mediated transformation method. This is the first demonstration of taxadiene production in filamentous fungi, and the approach presented in this study provides a new method for microbial production of Taxol.